2013
DOI: 10.1007/s00412-013-0400-6
|View full text |Cite
|
Sign up to set email alerts
|

A telomerase-independent component of telomere loss in chromatin assembly factor 1 mutants of Arabidopsis thaliana

Abstract: Dysfunction of chromatin assembly factor 1 in FASCIATA mutants (fas) of Arabidopsis thaliana results in progressive loss of telomeric DNA. Although replicative telomere shortening is typically associated with incomplete resynthesis of their ends by telomerase, no change in telomerase activity could be detected in vitro in extracts from fas mutants. Besides a possible telomerase malfunction, the telomere shortening in fas mutants could presumably be due to problems with conventional replication of telomeres. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…However, there is a loss of telomere sequences, although it is produced by a different mechanism from that responsible for the loss of 45S rDNA repeats (Muchová et al, 2015). Jaške et al (2013), after analyzing single tert (telomerase reverse transcriptase) and fas mutants, and the corresponding double mutants, concluded that the progressive loss of telomeric DNA along generations in fas mutants is partially due to a suboptimal function of telomerase, but they also assumed that a further mechanism that contributes to telomere shortening in fas mutants must exist. The existence of telomeric acentric fragments in fas1-4 anaphases ( Figure 1N ) and the enhanced frequency of these fragments in the double mutant fas1-4 rad51 ( Figure 3 ) suggest the involvement of a RAD51-independent mechanism in telomere shortening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a loss of telomere sequences, although it is produced by a different mechanism from that responsible for the loss of 45S rDNA repeats (Muchová et al, 2015). Jaške et al (2013), after analyzing single tert (telomerase reverse transcriptase) and fas mutants, and the corresponding double mutants, concluded that the progressive loss of telomeric DNA along generations in fas mutants is partially due to a suboptimal function of telomerase, but they also assumed that a further mechanism that contributes to telomere shortening in fas mutants must exist. The existence of telomeric acentric fragments in fas1-4 anaphases ( Figure 1N ) and the enhanced frequency of these fragments in the double mutant fas1-4 rad51 ( Figure 3 ) suggest the involvement of a RAD51-independent mechanism in telomere shortening.…”
Section: Discussionmentioning
confidence: 99%
“…They also present high levels of H2AX phosphorylation, a marker of DNA double-strand breaks (DSBs), and increased RAD51 expression compared with wild-type (WT) (Takeda et al, 2004; Endo et al, 2006; Kirik et al, 2006; Ono et al, 2006; Schönrock et al, 2006; Ramirez-Parra and Gutierrez, 2007b). Recently, it has been reported that in fas mutants there is also a specific and transgenerational loss of 45S rDNA and telomeric sequences (Mozgová et al, 2010; Jaške et al, 2013; Muchová et al, 2015; Pavlištová et al, 2016). The loss of these sequences is produced during the cell division and it does not occur during meiosis (Muchová et al, 2015; Varas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fas1 mutants also show an immediate telomere shortening and dysfunction, although telomerase activity is not altered. Surprisingly, the fas1;tert double mutants show even more telomere shortening than the single tert mutant [Jaske et al, 2013], suggesting a complex mechanism to explain the role of CAF-1 in telomere maintenance.…”
Section: Caf-1 (Chromatin Assembly Factor 1)mentioning
confidence: 99%
“…Although plants are more tolerant to defects in CAF-1 function than mammals, alteration in the H3.1/H3.3 balance seems to be highly deleterious for plant development, as revealed by the pleiotropic phenotype of fas1 , fas2 , and msi1 mutants, encoding each of the three CAF-1 subunits (Kaya et al, 2001; Hennig et al, 2003; Ramirez-Parra and Gutierrez, 2007a). Thus, fas1 mutants show increased homologous recombination, limited TE silencing, telomere shortening, and loss of 45S rDNA repeats (Endo et al, 2006; Kirik et al, 2006; Ono et al, 2006; Schonrock et al, 2006; Mozgova et al, 2010; Jaske et al, 2013). Likewise, asf1a, b double mutants exhibit a S-phase delay and up-regulation of checkpoint genes, such as ATM , ATR , and PARP1 (Zhu et al, 2011).…”
Section: Genome Replication Events and Chromatin Modifications (S)mentioning
confidence: 99%